2008
DOI: 10.1292/jvms.70.681
|View full text |Cite
|
Sign up to set email alerts
|

Regulated upon Activation Normal T-Cell Expressed and Secreted (RANTES) Contributes to Abortion Caused by Brucella abortus Infection in Pregnant Mice

Abstract: ABSTRACT. Brucella abortus (B. abortus) is a facultative intracellular pathogen that can survive inside macrophages and trophoblast giant cells, and the causative agent of brucellosis. In the present study, we found that production of regulated upon activation normal T-cell expressed and secreted (RANTES) due to B. abortus infection contributes to abortion in pregnant mice. B. abortus infected pregnant interferon-γ (IFN-γ) knockout mice died within 15 days of infection, but non-pregnant IFN-γ knockout mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 34 publications
(31 reference statements)
0
38
0
Order By: Relevance
“…In parallel, abortion is the main clinical symptom of brucellosis in cattle, but little is known about the molecular mechanism. In a recent publication, it was demonstrated that the increased expression of RANTES contributes to abortion in B. abortus -infected pregnant mice (Watanabe et al, 2008). This finding enables speculation that the increase rate of abortion induced in S cows after challenging with B. abortus (Harmon et al, 1985) could be in part due to the increased expression of RANTES gene.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, abortion is the main clinical symptom of brucellosis in cattle, but little is known about the molecular mechanism. In a recent publication, it was demonstrated that the increased expression of RANTES contributes to abortion in B. abortus -infected pregnant mice (Watanabe et al, 2008). This finding enables speculation that the increase rate of abortion induced in S cows after challenging with B. abortus (Harmon et al, 1985) could be in part due to the increased expression of RANTES gene.…”
Section: Discussionmentioning
confidence: 99%
“…routes barely induce physiopathological symptoms at early stages of infection. The absence of obvious clinical signs correlates with: i) normal blood cell and platelet counts; ii) the lack of a recruitment of proinflammatory cells at the site of infection; iii) the presence of minimal levels of serum IL-1β, TNF-α, IL-10 and IL-6; iv) very low amounts of MCP-1 and RANTES chemokines [48,137]; and, v) the absence of synthesis and degradation of fibrinogen and coagulopathies [48]. IL-10 is not detected in serum and its corresponding transcript only appears after 3 days of infection [126].…”
Section: Physiopathologymentioning
confidence: 99%
“…This suggests that the regulatory role of IL-10 is minor or irrelevant at early times of Brucella infection. At these early times, INF-γ and IL-12, are barely detected in serum or cell extracts and these cytokines become evident only during the next infection phase [63,135,137,138,141]. However, the low levels of INF-γ and IL-12 are not unique to early Brucella infections, since they are also observed at the onset of murine salmonellosis [142].…”
Section: Physiopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…[65][66][67] Similarly, CCL5 (RANTES) production in response to Brucella abortus correlated with IFN-g induction and contributed to abortion in mice. 68 Two polymorphisms of CCL5 in either the mother or the product would have opposite effects on congenital toxoplasmosis occurrence or pathology: the À28 C/G or G/G would be protective against infection, but without proper control it could relate to sterile abortion. 69 On the contrary, carriers of the À403A allele would have low CCL5 levels and thus people with this allele would have higher risk of vertical transmission.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%